Validating the Demand Control Support Questionnaire among white-collar employees in Switzerland and the United States - Mauss, Daniel; Herr, Raphael (Journal of occupational medicine and toxicology, 2018)
The Demand Control Support Questionnaire (DCSQ) is an established self-reported tool to measure a stressful work environment. Validated German and English versions are however currently missing. The aim of this study was therefore to evaluate the psychometric properties of German and English versions of the DCSQ among white-collar employees in Switzerland and the US.
Gesehen am 04.05.2020